Ultrastructure characters and partial mtDNA-COI haplotypes of Asian corn borer, Ostrinia furnacalis (Guenée) (Lepidoptera: Crambidae) from Indonesia - Ahmad Taufiq Arminudin; Suputa; Arman Wijonarko; Y. Andi Trisyono (Society for Indonesian Biodiversity, 2020)
Abstract. Arminudin AT, Suputa, Wijonarko A, Trisyono YA. 2020. Ultrastructure characters and partial mtDNA-COI haplotypes of Asian corn borer, Ostrinia furnacalis (Guenée) (Lepidoptera: Crambidae) from Indonesia. Biodiversitas 21: 2914-2922. In addition to the confirmation of the species of corn borer, we analyzed the relationship of Ostrinia furnacalis in Indonesia with that in other countries. Moths of O. furnacalis were collected from several areas in Java and Sumatra islands of Indonesia. Forewing and labial palpi scales were investigated under Scanning Electron Microscopy observation. A 658 bp of O. furnacalis partial COI gene sequences of 1480-2138 nucleotides were downloaded from GenBank and BOLD system databases. The ridge lamellae and window characters as unique ultrastructure characters of scale were further supported by the COI gene analysis. High similarity was observed between the Java and the Philippines specimens, but they were a different haplotype compared with Sumatra’s specimen. The results could provide the baseline data on the genetic variation of O. furnacalis in Indonesia.